2011
DOI: 10.1016/j.jss.2009.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation-Induced Intestinal Edema and Related Dysfunction: State of the Science

Abstract: High volume resuscitation and damage control surgical methods, while responsible for significantly decreasing morbidity and mortality from traumatic injuries, are associated with pathophysiological derangements that lead to subsequent end organ edema and dysfunction. Alterations in hydrostatic and oncotic pressures frequently result in intestinal edema and subsequent dysfunction. The purpose of this review is to examine the principles involved in the development of intestinal edema, current and historical mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 98 publications
0
46
0
Order By: Relevance
“…[16] To achieve this goal, HS strategy has been designed as the optimal therapeutic modality to attenuate the postoperative intestine edema after major operation or severe trauma. [17] The present study was conducted to determine if HS intragastric injection would reduce the postoperative intestine edema so as to promote intestinal function recovery in patients undergoing major upper gastrointestinal surgery, which has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] To achieve this goal, HS strategy has been designed as the optimal therapeutic modality to attenuate the postoperative intestine edema after major operation or severe trauma. [17] The present study was conducted to determine if HS intragastric injection would reduce the postoperative intestine edema so as to promote intestinal function recovery in patients undergoing major upper gastrointestinal surgery, which has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…[8,9] Because of the intestinal mucosal edema causing significant pathogenesis characterized by structural changes after injury, attention has been directed to specific care that might improve intestinal edema and intestinal transit.…”
Section: Introductionmentioning
confidence: 99%
“…(6, 33, 34) Systemically, the incidence of pulmonary complications, gastrointestinal dysmotility, and coagulation disturbances are higher as the volume of early crystalloid infusion is increased. Even when controlling for shock and severity of injury, the volume of crystalloid infused is associated with increased risk of developing intra-abdominal hypertension and abdominal compartment syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…At about this time, damage control laparotomy was first described and also began gaining widespread use. 20,21 The combination of these two treatment modalities in severely injured trauma patients resulted in the inability to close the abdominal wall due to massive intestinal and retroperitoneal edema, 26 which often persisted well after hemorrhagic shock was corrected. In 2003, Balogh et al demonstrated an association between supra-normal resuscitation and increased incidences of abdominal compartment syndrome, multiple organ failure, and mortality.…”
Section: Pharmacologic Treatment Optionsmentioning
confidence: 99%